Narrative synthesis of psychological and coping responses towards emerging infectious disease outbreaks in the general population: practical considerations for the COVID-19 pandemic - Chew, QH; Wei, KC; Vasoo, S; Chua, HC; Sim, K (Singapore medical journal, 2020)
Emerging infectious disease outbreaks, such as the present coronavirus disease 2019 (COVID-19) pandemic, often have a psychological impact on the well-being of the general population, including survivors and caregivers. Our study aimed to synthesise extant literature regarding the combined psychological responses and coping methods used by the general population in past outbreaks. We conducted a narrative synthesis of the published literature over the last two decades with a quality appraisal of included articles that reported both psychological responses and coping strategies within infectious disease outbreaks. A total of 144 papers were identified from the search, 24 of which were included in the review. Overall, 18 studies examined the psychosocial responses of the general population towards the severe acute respiratory syndrome epidemic, four studies focused on the Ebola epidemic and two studies covered the H1N1 outbreak. Common themes in psychological responses included anxiety/fears, depression, anger, guilt, grief and loss, post-traumatic stress and stigmatisation, but also a greater sense of empowerment and compassion towards others. Coping strategies adopted included problem-focused coping (seeking alternatives, self- and other-preservation), seeking social support, avoidance, and positive appraisal of the situation. Amid the range of psychosocial responses seen in past infectious disease outbreaks, practical considerations for the current COVID-19 pandemic need to focus on the individual in the context of the larger social environment, with an emphasis on raising awareness of the range of possible psychosocial responses, access to psychological help, self-care, empowering self-support groups and sustained engagement with updated, reliable information about the outbreak.